Initial description and evaluation of EDS ECHO: An international effort to improve care for people with the Ehlers‐Danlos syndromes and hypermobility spectrum disorders. Issue 4 (25th November 2021) - Schubart, Jane R.; Bascom, Rebecca; Francomano, Clair A.; Bloom, Lara; Hakim, Alan J.
Abstract: The Ehlers‐Danlos Society Extension for Community Health Care Outcomes (EDS ECHO) is a portfolio of teleconferencing programs developed around the principles and practices of Project ECHO®, aimed at increasing awareness of Ehlers‐Danlos syndromes (EDS) and hypermobility spectrum disorders (HSD) among clinicians, enhancing their confidence in the assessment and management of these complex conditions, and generating networks of clinicians across specialties. We assessed the outcomes of the first EDS ECHO program, launched in April 2019, with two hub locations: Indiana University Health, Indianapolis, Indiana, USA, and The Royal Society of Medicine, London, UK. Clinicians were surveyed before and 6 months after their participation. We describe the initial outcomes of the first four EDS ECHO programs, each comprising nine sessions. Participants reported increased levels of knowledge and confidence in providing care (93% and 95%, respectively) and an increase in referral network participation (65%). Additionally, 80% reported that their interest in EDS and HSD increased; 57% reporting a great increase. Also, 59% reported a decrease in feeling overwhelmed by EDS and HSD, and nearly half reported a decrease in their level of frustration because of participating in EDS ECHO. Clinicians participating in EDS ECHO programs know more, have more confidence in their ability to provide care, and feel energized by their participation.